Cesarean hysterectomy post - Calderón Morales, Jorge (2015)
From 1 January 1981 until December 31, 1986, 78 post-emergency cesarean at the National Hospital Edgardo Rebagliati Martins (HNERM), as last surgical means to preserve the life of the patient hysterectomy was performed. The post.cesárea hysterectomies in our medical center, corresponding to 8 per 10,000 births to 5 per 1,000 Caesareans. Maternal mortality was about 78 cases three.